Karakteristik dan Perilaku Masyarakat tentang Penyediaan Air Bersih di Kelurahan Keramasan Kecamatan Kertapati Kota Palembang - Rusdiana, Ida; Kamsul Kamsul; Intan Kumalasari (Pusat Riset dan Inovasi Nasional, 2025)
Clean water is a basic human need to achieve a healthy standard of living. Human survival is greatly influenced by the quality of water and the availability of water in sufficient quantities. In Keramasan Village, there are still many people who have bad habits in providing clean water. People use the river as a place to bathe, wash clothes, wash dishes and throw away garbage.The level of knowledge, attitudes and actions of the community regarding the provision of clean water in Keramasan Village, Kertapati District, Palembang City.This type of research is descriptive research with a cross-sectional design. The population in this study were 159 families living in RT 11 and RT 12 in Keramasan Village. The total sample of respondents in this study was 67 families. Sampling was carried out using a random sampling technique, which aims to ensure that the sample can represent all families.From the results of the study on the provision of clean water, the level of knowledge of 46.3% of respondents had a low level of knowledge, in contrast to the attitude of 67.1% of respondents showing a good attitude. and 59.7% of respondents have poor actions regarding the provision of clean water.From the results obtained, it can be concluded that the community in Keramasan sub-district regarding the provision of clean water, at the level of knowledge, most respondents still have a low level of knowledge, most respondents already have attitudes in the good category, and most people have actions in the bad category.